Naše izkušnje z epiduralno porodno analgezijo - Reš-Muravec, Uršula (Zdravniški vestnik, 2003)
Background. To evaluate the effects of regional labour analgesia used at the Hospitalfor Gynecology and Obstetrics in Postojna, Slovenia, in the year 2002.Patients and methods. In this retrospective study we enrolled 294 parturients who delivered in the year 2002 in the Postojna Maternity Hospital:in group 1 there were 247 parturients in whom three different regional analgesic techniques (study group) were used at labour, in group 2 there were 247 parturients in whom regional analgesia was not used (control group). In the first step the two groups were compared in terms of maternal demographic data, duration and outcome of labour and 1' and 5' Apgar scores. In the second step the three regional analgesic groups were compared in terms of the course and outcome of labour, fetal condition, side and adverse effectsof regional analgesic techniques, and patient satisfaction with a particular analgesic technique. Results. Regional labour analgesia was used in247 (14%) of the 1048 women who delivered in 2002: epidural analgesia (EPI) was performed in 51.0%, combined spinal-epidural (CSE) in 42.2% and spinal analgesia (SA) in 68% of cases. The women in the regional analgesia group weresignificantly older, more educated, more often nulliparous and accompaniedby their partner at labour than the women in the control group. Further, the duration of labour was significantly longer, oxytocin more frequently administered than in the control group. In terms of labour outcome there were no differences in the Cesarean section rates and 1- and 5-min Apgarscores minutes, but and the vacuum extraction rate was significantly higher in the regional analgesia group. Among the three regional analgesia techniques used, there were no statistically significant differences observed in terms of labour duration and outcome, and Apgar scores. The patient satisfaction was greatest with CSE. (Abstract truncated at 2000 characters).
Keywords: Analgesia, Epidural; Analgesia, Obstetrical; Analgezija epiduralna; Analgezija porodniška; bolečina; Carski rez; Cesarean Section; childbirth; epiduralna analgezija; porod; porodništvo; Vacuum Extraction, Obstetrical; Vakuumska ekstrakcija porodniška